The economy, the government and trade union responsibilities, 1979 (London, 1979)
1979 1974-79 "The economy, the government and trade union responsibilities, 1979" [BW0094], 1979, Trades Union Congress On 22 January, 1979 public sector unions held a "Day of Action" against government pay controls, in which they held a 24-hour strike and marched to demand a £60 per week minimum wage. Many workers stayed out indefinitely after that day. After lengthy negotiations, the TUC and Government issued this joint statement, known as the Concordat, on February 14, 1979. The strikes took some time to cease. Local authority workers settled in February and the health workers in March. This period was termed 'the Winter of Discontent' by the media.